Inhibition of enzymes important for Alzheimer’s disease by antioxidant extracts prepared from 15 New Zealand medicinal trees and bushes - Mohd Hafiz Abd Majid; Silva, Filipa V M (2020)
Alzheimer’s disease is characterised by progressive mental deterioration, related to ageing and senility. Thirty methanol and ethyl acetate extracts from 15 native New Zealand trees and bushes were produced and tested for the inhibition of three enzymes related to neurotransmission: acetylcholinesterase (AChE), butyrylcholinesterase (BChE) and beta-secretase (BACE). In addition the IC50 for the antioxidant potential of the extracts was determined. Weinmannia racemosa and Kunzea ericoides were effective inhibitors of AChE-BChE and beta-secretase, respectively. The IC50 for W. racemosa extracts against AChE and BChE ranged between 8.09 μg/mL and 37.07 μg/mL. The ethyl acetate extract of Schefflera digitata was also an effective inhibitor of BChE (IC50 = 25.38 μg/mL). K. ericoides IC50 for beta-secretase were 29.05 μg/mL and 36.40 μg/ml. The highest radical scavenging activity (RSA) was detected in the methanol extract of Aristotelia serrata (IC50 = 2.34 μg/mL), followed by both extracts of Hebe stricta and W. racemosa, and last the methanol extracts of K. ericoides and Pomaderris kumeraho, which presented higher RSA than the reference antioxidant (IC50 <12.0 μg/mL). W. racemosa showed inhibitory activity against AChE and BChE enzymes and antioxidant activity, which suggests these extracts may have potential for application in patients suffering from Alzheimer's disease and other dementias.